2017
DOI: 10.1155/2017/2492483
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitric Oxide and Prostaglandins in the Sustained Antihypertensive Effects of Acanthospermum hispidum DC. on Ovariectomized Rats with Renovascular Hypertension

Abstract: Although Acanthospermum hispidum is used in Brazilian folk medicine as an antihypertensive, no study evaluated its effects on a renovascular hypertension and ovariectomy model. So, this study investigated the mechanisms involved in the antihypertensive effects of an ethanol-soluble fraction obtained from A. hispidum (ESAH) using two-kidney-one-clip hypertension in ovariectomized rats (2K1C plus OVT). ESAH was orally administered at doses of 30, 100, and 300 mg/kg, daily, for 28 days, after 5 weeks of surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The extracts of Acanthospermum hispidum capture the free radicals produced by DEN [ 29 ] by their phenolic compounds. Palozi et al [ 30 ] also reported a good antioxidant capacity of extracts of the aerial part of Acanthospermum hispidum in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of Acanthospermum hispidum capture the free radicals produced by DEN [ 29 ] by their phenolic compounds. Palozi et al [ 30 ] also reported a good antioxidant capacity of extracts of the aerial part of Acanthospermum hispidum in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies describe the chemical composition of the leaves or aerial parts of A. hispidum , showing mainly the presence of compounds from the flavonoid class, such as quercetin derivatives, cinnamic acids, such as chlorogenic acid derivatives and dicafeioilquinic acid derivatives, and terpenoids [19–22] . The presence of tannins, alkaloids, saponins, cardioactive glycosides, and anthraquinones has also been reported [23–26] .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies describe the chemical composition of the leaves or aerial parts of A. hispidum, showing mainly the presence of compounds from the flavonoid class, such as quercetin derivatives, cinnamic acids, such as chlorogenic acid derivatives and dicafeioilquinic acid derivatives, and terpenoids. [19][20][21][22] The presence of tannins, alkaloids, saponins, cardioactive glycosides, and anthraquinones has also been reported. [23][24][25][26] Corroborating what is described in the scientific literature, the phytochemical analysis performed on the crude extract and fractions of A. hispidum aerial parts revealed the presence of phenolic compounds, with hydroxycinnamic derivatives standing out.…”
Section: Characterization Of Crude Extract and Fractionsmentioning
confidence: 99%
“…Several studies have shown that A. hispidum has antibacterial and antiviral properties (Anani et al, 2000;Atindehou et al, 2004;Fleischer et al, 2003;Hoffman et al, 2004), abortifacient and teratogenic (Lemonica and Alvarenga, 1994), anti-malaria (Sanon et al, 2003), immunostimulatory (Summerfield and Sallmuller, 1998) antitrypanosomal, antileishmanial, antitrichomonal (Ganfon et al, 2012;Adepiti et al, 2014), Antihypertensive effects (Palozi et al, 2017), antioxidant and hepatoprotective (N'Do et al, 2018). It was reported that A. hispidum contains some chemicals such as sesquiterpenes and lactones (Jakupovic et al, 1986;Arena et al, 2011).…”
Section: Introductionmentioning
confidence: 99%